Critérios Éticos na Admissão a Cuidados Intensivos - COVID-19 - António Diogo Gonçalves dos Santos Rebelo Pereira (2022)
Objetive: The SARS-COV2 pandemic may be the first of many to overcrowd the national health services and because of that we think that is very important to know the opinion of health professionals, health researchers and future physicians about the ethical criteria to be used in situations where is not possible to assist all the patients. Methods: To carry out this study, we sent a questionnaire to health professionals at São João Hospital Centre (Porto, Portugal), health researchers (linked to the Faculty of Medicine of the University of Porto-FMUP or / and CINTESIS- Center for Research in Health Technologies and Services) and also to students of the fifth and sixth year of medicine at FMUP. Results: 230 fifth- and sixth-year medical students and 382 health professionals and researchers responded to this questionnaire. 93%(n=214) of the students and 91%(n=319) of the Professionals/Researchers believe that there should be universal, explicit, transparent ethical criteria, beyond clinical criteria, for admisson to intensive care in situations of absolute scarcity of resources. Conclusion: Age should not be the only criteria for admission on intensive care units because every patient has their own characteristics and must be evaluated as a whole. Fifth- and sixth-year medical students at FMUP already demonstrated critical thinking and a sense of medical ethical criteria that was similar to professionals/researchers.